Growth of micropropagated banana plants in function of substrate and controlled release fertilizer (Revista de Ciências Agroveterinárias, 2019)
The objective of this study was to evaluate the growth of micropropagated banana trees cv. BRS FHIA-18 in conditions of greenhouse with use of Basacote® and substrates. For the installation of the experiment, we used banana micropropagated plants cv. BRS FHIA-18. The treatments consisted of Basacote® concentrations (0, 3, 6 and 9 kgm-3 of substrate) and substrates: Plantmax® HT, Plantmax® HT + carbonized rice chaffe (CAC) and subsoil land + CAC. After 90 days of transplanting, we evaluated plant height (cm), root system length (cm), number of roots, and relationship between the dry weight (g) of shoot and roots.  Plantmax® HT substrate plus 3 kg m-3 Basacote® is the most suitable for the best growth of banana trees cv. BRS FHIA-18 in the acclimatization phase.
Keywords: Musa spp.; fertilization; acclimatization